Edible coating of chitosan ionically combined with κ-carrageenan maintains the bract and postharvest attributes of dragon fruit (Hylocereus undatus) - Thi Hanh Nguyen; P. Boonyaritthongchai; M. Buanong; Suriyan Supapvanich; C. Wongs‐Aree (International Food Research Journal, 2021)
Dragon fruit (Hylocereus undatus) has medicinal properties due to its rich antioxidant profile. Dragon fruit also has an attractive appearance of red peel and green bracts. However, shrivelling and weight loss, bract yellowing, and postharvest diseases are major challenges to the dragon fruit trade. The objective of the present work was, therefore, to formulate a coating composed of chitosan and κ-carrageenan for dragon fruits during storage at 10°C. The composite coating based on 1% chitosan (w/v) and 0.2% (w/v) κ-carrageenan with 0.75% (w/v) glycerol as a plasticiser effectively reduced the physiological weight loss and maintained the freshness of the dragon fruits, while increasing the phenolic content and maintaining the titratable acidity in the pulp. The composite coating delayed chlorophyll degradation by suppressing chlorophyllase and chlorophyll-degrading peroxidase, thereby maintaining the chlorophyll content (45.46 mg/100 g dry weight) and freshness of the bracts. However, the composite coating did not possess a strong effect on enhancing chitinase and β-1-3 glucanase activities of dragon fruits during storage and controlling disease symptoms.
Keywords: Botanical Research and Applications; Nanocomposite Films for Food Packaging; Polysaccharides and Plant Cell Walls